Front Cover: In Situ Generated DBU⋅HF Acts as a Fluorinating Agent in a Hexafluoroisobutylation Tandem Reaction: An Effective Route to 5, 5, 5, 5', 5', 5'‐Hexafluoroleucine (Eur. J. Org. Chem. 10/2023). Issue 10 (27th February 2023) - Naulet, Guillaume; Delamare, Aline; Guichard, Gilles; Compain, Guillaume
Abstract : The Front Cover illustrates the ability of DBU – the yellow tightrope walker – to preserve the fluoride nucleophilicity promoting the fluorination of a pentafluoroisobutenyl group – the five‐flower bouquet carried by the young lady – in a cascade reaction. In contrast, the alkali metals – the blue acrobats – precipitate with fluoride ions precluding a subsequent hydrofluorination. Cover created by Ludion. More information can be found in the Research Article by G. Guichard, G. Compain et al .